The role of teachers in developing multicultural education of religious tolerance in primary schools: literature study - Fauziah, Nursifa; Zakiah, Linda; Jannah, Hasbiya Miftahul; Elifas, Leonardo; Safitri, Nurrohmah (Jurnal Bidang Pendidikan Dasar, 2024)
This study aims to examine the role of teachers in developing tolerance among students. Tolerance is the ability to appreciate differences and resolve conflicts peacefully. Teachers have a very important role in shaping this attitude of tolerance through an inclusive learning approach, fostering universal values, and providing examples of tolerance behavior in everyday life. This research is a qualitative research with literature study. The subject and instrument of this research is the researcher himself by searching for relevant sources. Data were collected through content analysis which involved several steps, such as determining the problem, developing a framework, developing methodological tools, data analysis, and data interpretation.Â  The research findings show that teachers who practice multicultural education-oriented learning approaches and integrate subject matter with tolerance values are able to have a significant impact in shaping students' tolerance attitudes. This multicultural education aims to appreciate and understand diversity in society.